1974
DOI: 10.1172/jci107747
|View full text |Cite
|
Sign up to set email alerts
|

High-Affinity Accumulation of Chloroquine by Mouse Erythrocytes Infected with Plasmodium berghei

Abstract: A B S T R A C T Washed erythrocytes infected with chloroquine-susceptible (CS) or with chloroquine-resistant (CR) P. berghei were used in model systems in vitro to study the accumulation of chloroquine with high affinity. The CS model could achieve distribution ratios (chloroquine in cells: chloroquine in medium) of 100 in the absence of substrate, 200-300 in the presence of 10 mM pyruvate or lactate, and over 600 in the presence of 1 mM glucose or glycerol. In comparable studies of the CR model, the distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 13 publications
4
40
0
Order By: Relevance
“…However, as expected, at higher CQ concentrations, a slight alkalinization of the food vacuole became apparent. An analogous study of CQ accumulation in Plasmodium berghei attributed the effect of external pH to a non-specific interaction (Fitch et al, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…However, as expected, at higher CQ concentrations, a slight alkalinization of the food vacuole became apparent. An analogous study of CQ accumulation in Plasmodium berghei attributed the effect of external pH to a non-specific interaction (Fitch et al, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…Chloroquine resistance is thought to arise, at least in part, from a decreased level of chloroquine uptake, although some studies suggest that an alteration in the drug target may also be involved [30,36,45]. Chloroquine resistance can be reversed in itro and in animal models by co-administration of compounds such as verapamil, chlorpromazine and desipramine [46][47][48].…”
Section: Resistance-modulating Agents Inhibit the Peroxidative Destrumentioning
confidence: 99%
“…1). We have previously reported that amodiaquine is accumulated more effectively than chloroquine by erythrocytes infected with P. berghei CR (chloroquine resistant) (10) or Plasmodium falciparum CR (5). We now report that mefloquine accumulation is undiminished in erythrocytes infected with P. berghei CR.…”
mentioning
confidence: 66%
“…The parasites, the characteristics of erythrocytes infected with them, and the methods used to obtain and prepare infected erythrocytes for study have been described previously (3,12). The P. berghei CR line is resistant to 40 mg of chloroquine per kg of body weight of the mouse daily (12).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation